Optimizing Small and Medium Enterprises' Marketing Performance through RBV: A Local Wisdom-Based Approach - Nur Afifah (STIE AMKOP, 2023)
MSMEs play a role in increasing Indonesia's economic growth through the absorption of labor. Likewise in West Kalimantan. The aim of this research is to determine the factors that influence local wisdom-based MSMEs in improving marketing performance from the perspective of RBV implementation. Data was collected from 100 snack food MSME respondents in Pontianak City, as samples in research to test the proposed model, using structural equation modeling (SEM)-PLS modeling software. The results of the research show that market orientation and entrepreneurial orientation influence marketing performance which is mediated by marketing capabilities, so it is known that entrepreneurial orientation can improve marketing capabilities, and ultimately will also improve the marketing performance of culinary MSMEs with local wisdom products in Pontianak City. Keywords: Local Wisdom, MSMEs, Marketer Performance